Inducing Acute Traumatic Coagulopathy In Vitro: The Effects of Activated Protein C on Healthy Human Whole Blood - Howard, Benjamin M. (PLoS One, 2016)
INTRODUCTION: Acute traumatic coagulopathy has been associated with shock and tissue injury, and may be mediated via activation of the protein C pathway. Patients with acute traumatic coagulopathy have prolonged PT and PTT, and decreased activity of factors V and VIII; they are also hypocoagulable by thromboelastometry (ROTEM) and other viscoelastic assays. To test the etiology of this phenomenon, we hypothesized that such coagulopathy could be induced in vitro in healthy human blood with the addition of activated protein C (aPC). METHODS: Whole blood was collected from 20 healthy human subjects, and was “spiked” with increasing concentrations of purified human aPC (control, 75, 300, 2000 ng/mL). PT/PTT, factor activity assays, and ROTEM were performed on each sample. Mixed effect regression modeling was performed to assess the association of aPC concentration with PT/PTT, factor activity, and ROTEM parameters. RESULTS: In all subjects, increasing concentrations of aPC produced ROTEM tracings consistent with traumatic coagulopathy. ROTEM EXTEM parameters differed significantly by aPC concentration, with stepwise prolongation of clotting time (CT) and clot formation time (CFT), decreased alpha angle (α), impaired early clot formation (a10 and a20), and reduced maximum clot firmness (MCF). PT and PTT were significantly prolonged at higher aPC concentrations, with corresponding significant decreases in factor V and VIII activity. CONCLUSION: A phenotype of acute traumatic coagulopathy can be induced in healthy blood by the in vitro addition of aPC alone, as evidenced by viscoelastic measures and confirmed by conventional coagulation assays and factor activity. This may lend further mechanistic insight to the etiology of coagulation abnormalities in trauma, supporting the central role of the protein C pathway. Our findings also represent a model for future investigations in the diagnosis and treatment of acute traumatic coagulopathy.